Estimation of vehicle sideslip angle scheme using finite-time convergence algorithm. (12th August 2019) - Zhang, Peng; Liu, Feng; Sheng, Fei
Since vehicle sideslip angle estimation scheme is a real-time application, in essence, the scheme's convergence speed is an issue worth attention. This paper presents a new estimator scheme whose output is theoretically guaranteed to converge to real value in the desired interval, and this makes it possible to be a more reasonable solution for application such as electronic stabilisation control (ESC). To improve the accuracy and adaptive capability of this scheme, the unmodelled error compensating mechanism is adopted. Then experiment results based on veDYNA vehicle dynamic simulation environment validate the applicability of the method.